Do Macroeconomic Variables Affect Deposits in Shariah Banks? - Ayunseh Retno Harini; Mahrus Lutfi Adi Kurniawan; Budi Jaya Putra (Islamic Economics Journal, 2024)
Banks are intermediary institutions that collect funds from the public and channel them back in the form of credit and the funds collected are third party funds (TPF) which are the largest source of funds relied on by banks, including sharia banking. The challenge of sharia banking is to expand market share. Currently in Indonesia the banking market share is dominated by conventional banking. Increasing market share will increase savings in sharia banking and strengthen sharia banking as an intermediation institution. The research aims to identify the influence of macroeconomic variables on deposits in sharia banking. The research uses time-series data 2012: Q1 - 2022: Q1 and the ARDL method to estimate the short- and long-term influence of macroeconomic variables on TPF. The research results show that there are two variables that influence the short and long term, namely the GDP variable and the exchange rate. Meanwhile, inflation and interest rate variables only have an effect in the short term. The implications of the research show that increasing economic growth must be followed by increasing people’s income and the stability of the rupiah exchange rate will increase people’s deposits or savings in sharia banking.